Characterization of Cholesterol Homeostasis in Telomerase-immortalized Tangier Disease Fibroblasts Reveals Marked Phenotype Variability - Kannenberg, Frank (American Society for Biochemistry and Molecular Biology, 2013)
We compared the consequences of an ABCA1 mutation that produced an apparent lack of atherosclerosis (Tangier family 1, N935S) with an ABCA1 mutation with functional ABCA1 knockout that was associated with severe atherosclerosis (Tangier family 2, Leu(548):Leu(575)-End), using primary and telomerase-immortalized fibroblasts. Telomerase-immortalized Tangier fibroblasts of family 1 (TT1) showed 30% residual cholesterol efflux capacity in response to apolipoprotein A-I, whereas telomerase-immortalized Tangier fibroblasts of family 2 (TT2) showed only 20%. However, there were a number of secondary differences that were often stronger and may help to explain the more rapid development of atherosclerosis in family 2. First, the total cellular cholesterol content increase was 2–3-fold and 3–5-fold in TT1 and TT2 cells, respectively. The corresponding increase in esterified cholesterol concentration was 10- and 40-fold, respectively. Second, 24-, 25-, and 27-hydroxycholesterol concentrations were moderately increased in TT1 cells, but were increased as much as 200-fold in TT2 cells. Third, cholesterol biosynthesis was moderately decreased in TT1 cells, but was markedly decreased in TT2 cells. Fourth, potentially atheroprotective LXR-dependent SREBP1c signaling was normal in TT1, but was rather suppressed in TT2 cells. Cultivated primary Tangier fibroblasts were characterized by premature aging in culture and were associated with less obvious biochemical differences. In summary, these results may help to understand the differential atherosclerotic susceptibility in Tangier disease and further demonstrate the usefulness of telomerase-immortalized cells in studying this cellular phenotype. The data support the contention that side chain-oxidized oxysterols are strong suppressors of cholesterol biosynthesis under specific pathological conditions in humans.